Integrating Artificial Intelligence in Islamic Religious Education and Its Impact on Students’ Learning Motivation - Ibnu Abbas; Vishal Yadav; Sanya Desai (Islamic Studies in the World, 2026)
Background. The increasing use of artificial intelligence (AI) in education has created new opportunities for more interactive and flexible learning environments. In Islamic Religious Education (IRE), AI offers innovative ways to access and understand religious knowledge, yet its influence on students’ learning motivation requires further investigation. Purpose. This study aimed to examine how the integration of artificial intelligence in Islamic Religious Education affects students’ learning motivation at SMK Muhammadiyah Berau. Method.  A qualitative research design was employed using interviews, classroom observations, and document analysis involving teachers, students, and school administrators. The data were analyzed thematically to identify patterns of AI use and its impact on students’ motivation in IRE learning. Results. The findings indicate that AI supports students’ understanding of Islamic concepts by providing clearer explanations and learning assistance, which increases their confidence and participation in classroom activities. AI also encourages students to explore religious materials more actively. However, some students tend to rely too heavily on AI-generated answers, which can reduce critical thinking and reflective learning when not guided by teachers. Conclusion. The study concludes that AI can enhance students’ learning motivation in Islamic Religious Education when it is implemented with appropriate pedagogical guidance and ethical awareness. Teachers and schools play a crucial role in ensuring that AI is used to support meaningful, responsible, and value-based learning.